EFFECT OF GUIDED DISCOVERY LEARNING MODEL BASED COLLABORATION WITH FLASH MEDIA ON SCIENCE PROCESS SKILLS - Erna Pardede; Motlan .; Retno Dwi Suyanti (Jurnal Pendidikan Fisika, 2016)
This research aimed to determine is there any significant differences between Students’ Science Process Skill taught by using Collaboration Based Guided Discovery Technique using Flash Media with conventional learning. The sample of the research was taken by using cluster random sampling from around 2 classes consisting of 82 students. Experimental class was taught by using Based Guided Discovery Technique using Flash Media. Meanwhile control class was taught by using conventional teaching technique. The data analysis technique used independent T-test and correlation test with SPSS 17 at the significance level α = 0.05. The result of the research showed  that there were significant differences between students’ science process skill taught by using Collaboration Based Guided Discovery Technique using Flash Media with conventional learning.